Analisis Nilai Pendidikan Akhlak Dalam Memotivasi Semangat Belajar (Telaah Buku Catatan Perubahan Karya M. Hamka) - Munawaroh, Siti (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
This study aims to: 1.) find out the values ​​of moral education in motivating the spirit of learning in the Change Notebook, 2.) find out the form of motivation for learning in the Change Notebook. This study uses a qualitative research approach and the type of research is library research. The data collection technique uses a documentary study. The data for the study were taken from primary data sources and secondary data sources. The results of the study can be concluded that: 1.) the values ​​of moral education contained in the book of Changes by M. Hamka are the values ​​of moral education that can be used as motivation in learning, namely good morals towards Allah SWT and good morals towards others. Good morals towards Allah can be classified into three parts, namely: good intentions, doing good, and trusting. The value of education for others is classified into five parts, namely: multiply alms, strengthen ties of friendship, instill an attitude of tawadhu ', forgiving, and helping each other. 2.) the forms of motivation contained in M. Hamka's Notes of Change are: giving prizes, competition, and recognized goals.